Molecular Mechanisms and Applications of N-Acyl Homoserine Lactone-Mediated Quorum Sensing in Bacteria - Kumar, Lokender; Patel, Sanjay Kumar Singh; Kharga, Kusum; Kumar, Rajnish; Kumar, Pradeep; Pandohee, Jessica; Kulshresha, Sourabh; Harjai, Kusum; Chhibber, Sanjay (MDPI,CODEN, MOLEF, 2022)
Microbial biodiversity includes biotic and abiotic components that support all life forms by adapting to environmental conditions. Climate change, pollution, human activity, and natural calamities affect microbial biodiversity. Microbes have diverse growth conditions, physiology, and metabolism. Bacteria use signaling systems such as quorum sensing (QS) to regulate cellular interactions via small chemical signaling molecules which also help with adaptation under undesirable survival conditions. Proteobacteria use acyl-homoserine lactone (AHL) molecules as autoinducers to sense population density and modulate gene expression. The LuxI-type enzymes synthesize AHL molecules, while the LuxR-type proteins (AHL transcriptional regulators) bind to AHLs to regulate QS-dependent gene expression. Diverse AHLs have been identified, and the diversity extends to AHL synthases and AHL receptors. This review comprehensively explains the molecular diversity of AHL signaling components of Pseudomonas aeruginosa, Chromobacterium violaceum, Agrobacterium tumefaciens, and Escherichia coli. The regulatory mechanism of AHL signaling is also highlighted in this review, which adds to the current understanding of AHL signaling in Gram-negative bacteria. We summarize molecular diversity among well-studied QS systems and recent advances in the role of QS proteins in bacterial cellular signaling pathways. This review describes AHL-dependent QS details in bacteria that can be employed to understand their features, improve environmental adaptation, and develop broad biomolecule-based biotechnological applications.
This paper is submitted by the author of IIT (BHU), Varanasi, India
Keywords: acyl-homoserine lactone; Acyl-Butyrolactones; Bacterial Proteins; Gram-Negative Bacteria; Humans; Pseudomonas aeruginosa; Quorum Sensing; Transcription Factors